2022
DOI: 10.1177/1420326x221145862
|View full text |Cite
|
Sign up to set email alerts
|

A review on indoor environmental quality in sports facilities: Indoor air quality and ventilation during a pandemic

Abstract: Because of COVID-19, the indoor environmental quality (IEQ) in sports facilities has been a concern to environmental health practitioners. To develop an overall understanding of the available guidelines and standards and studies performed on IEQ in sports facilities, an extensive literature study was conducted, with the aim of identifying: (1) indicators that are being used to assess IEQ in different sports facilities; (2) indicators that are potentially interesting to be used to assess indoor air, in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 95 publications
2
5
0
Order By: Relevance
“…Findings by Huang et al (2022) entail that evaluating the environmental performance of sports buildings allows the identification of energy-efficient technologies, strategies and practices that can reduce energy consumption and contribute to overall sustainability goals. This is in line with the study by Zhang et al (2022), which found that the indoor environment of sports buildings directly impacts the well-being and comfort of occupants, including athletes, spectators and staff. Evaluating the environmental performance of sports buildings provides an opportunity to engage the community in sustainable practices and inspire behaviour change (Jung et al , 2021; Sant'Anna et al , 2018).…”
Section: The Analysis and Discussion Of Findingssupporting
confidence: 91%
“…Findings by Huang et al (2022) entail that evaluating the environmental performance of sports buildings allows the identification of energy-efficient technologies, strategies and practices that can reduce energy consumption and contribute to overall sustainability goals. This is in line with the study by Zhang et al (2022), which found that the indoor environment of sports buildings directly impacts the well-being and comfort of occupants, including athletes, spectators and staff. Evaluating the environmental performance of sports buildings provides an opportunity to engage the community in sustainable practices and inspire behaviour change (Jung et al , 2021; Sant'Anna et al , 2018).…”
Section: The Analysis and Discussion Of Findingssupporting
confidence: 91%
“…28,46 Concentrations of air pollutants inside homes are greatly affected by different factors such as physical and chemical structures of the pollutants (such as size and constituent of the PM), indoor and outdoor sources of air pollution and the design and location of the residential building. 34,47 Higher ambient temperature and humidity in the Gulf Cooperation Council (GCC) countries have contributed to the increase in time spent indoors. 48 Generally, residences in the Middle East are located in areas of heavy air pollution sources (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore imperative to strike a balance between air changes per hour (ACH) ventilation and space constraints and resource availability. [2][3][4][5] Furthermore, recent studies, for instance a review done by Zhang et al, 6 and Pei and Taylor, 7 have highlighted the importance of environmental factors in the spread of COVID-19. One study found that indoor environments with poor ventilation may increase the risk of transmission by allowing for the accumulation of viral particles in the air.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that indoor environments with poor ventilation may increase the risk of transmission by allowing for the accumulation of viral particles in the air. 6 Similarly, research has shown that airflow patterns can influence the transmission of the virus, with stagnant air increasing the risk of transmission. 7 In a report issued on 9 July 2020, the World Health Organization (WHO) 8 emphasized that respiratory droplets, ranging from 5 to 10 μm in diameter, serve as the primary mode of transmission.…”
Section: Introductionmentioning
confidence: 99%